Tornar-se professor de sociologia no ensino médio: identidades em construção - Almeida, Francisca Rosânia Ferreira de (2013)
Facing the situation of a growing publicization of discredit in the brazilian teaching career, plus the recent reintroduction of Sociology at the secondary level educational curriculum (Law 11,684/2008), this paper aims to analyze the sense and meanings that Sociology teachers attach to their daily teaching duties. The data collection was made possible through the use of questionnaires and semistructured interviews with 13 Sociology teachers from public schools, from the public educational network of Ceará, deriving from graduation degree courses at Social Science, from Federal University of Ceará and State University of Ceará, approved at the last public selection (concurrence) held in 2010. This present study discusses the sociology teaching in Basic Education From the analysis of the subjects studied pathwyas, since their university formation until their teaching daily routine in schools, reference to the processes that shaped their professional identity. The results of this research points to the following issues: the identity of sociology at Basic Education is being formed at the same time as teachers are forming their own identity processes before teaching; academic-professional sociology teachers are marked not only by social issues that afflict general Brazilian education, but also by inherent problems to the discipline and its school institutionalization; the meaning assigned by Sociology teachers to their teaching refers as well to the discipline role in Education, the evaluation of their activities and their job level satisfaction.